Development of a quantitative evaluation method in occupational therapy exercise for upper limb motor function rehabilitation / Hokyoo Lee ...[et al.] - Hokyoo, Lee; Ab Patar, Mohd Nor Azmi; Takashi, Komeda; Mahmud, Jamaluddin; Takahashi, Yoshiyuki (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Rehabilitation exercises required to sustain a motivation amongst patients and demands a quantitative in rehabilitation field. In this study, we developed a measuring equipment for upper limb motor function rehabilitation using optical sensor to improvise these problems. This system consisted of an optical sensor device, a personal computer and automatic calculated software for upper limb position. The measuring equipment was designed to measure the optical sensor position and movement length during the task of sanding movement and wiping movement. The movement positions were calculated based on the motion captured by optical sensors. We found that the accuracy of the optical sensor trajectories was similar in all actual measured value. These results are proposed to be very beneficial in the development of rehabilitation training programs and evaluation methods for patients who needs upper limb motor functions.